The Cambridge handbook of race and surveillance - Kwet, Michael (Cambridge law handbooks, 2023)
Featuring chapters authored by leading scholars in the fields of criminology, critical race studies, history, and more, The Cambridge Handbook of Race and Surveillance cuts across history and geography to provide a detailed examination of how race and surveillance intersect throughout space and time. The volume reviews surveillance technology from the days of colonial conquest to the digital era, focusing on countries such as the United States, Canada, the UK, South Africa, the Philippines, India, Brazil, and Palestine. Weaving together narratives on how technology and surveillance have developed over time to reinforce racial discrimination, the book delves into the often-overlooked origins of racial surveillance, from skin branding, cranial measurements, and fingerprinting to contemporary manifestations in big data, commercial surveillance, and predictive policing. Lucid, accessible, and expertly researched, this handbook provides a crucial investigation of issues spanning history and at the forefront of contemporary life.